Highly wear-resistant zeolite molded body and method for producing same

A method using clay and silica sol binders with controlled density and sphericity enhances zeolite molded bodies' abrasion resistance and fluidity, addressing equipment issues in adsorption towers.

JP7600640B2Active Publication Date: 2024-12-17TOSOH CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020195983
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-28
Filing Date
2020-11-26
Publication Date
2024-12-17
Estimated Expiration
2040-11-26

AI Technical Summary

Technical Problem

Existing zeolite molded bodies lack sufficient abrasion resistance and fluidity, leading to equipment trouble and prolonged filling/recovery times in adsorption towers.

Method used

A manufacturing method using two types of binders, clay and silica sol, with specific ratios and additives, to enhance wear resistance and fluidity, including controlled loose bulk density and sphericity.

Benefits of technology

The resulting zeolite molded bodies exhibit high wear resistance and fluidity, enabling efficient use in adsorption/separation applications without equipment issues.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a highly wear-resistant zeolite molded product having higher wear resistance and fluidity than conventional zeolite molded products and having high fluidity, and a method for producing the same.SOLUTION: A highly wear-resistant zeolite molded product, which comprises 35 to 70 pts.wt. of clay, 5 to 40 pts.wt. of silica sol and 0.5 to 10 pts.wt. of water-soluble sodium salt, relative to 100 pts.wt. of zeolite, and has a wear resistance of 90%, an angle of repose of 40° or less, a loose bulk density on the surface of the zeolite molded product of 0.5 kg / L or more, and a degree of sphericity of 1 to 3, the highly wear-resistant zeolite molded product being characterized in that it comprises at least one type of zeolite that has a Si / Al2 ratio of 10 to 100000 and a water adsorption amount of 10 (g / 100 g) or less under the conditions of 25°C and a relative pressure of 0.5. There is also provided a method for producing the highly wear-resistant zeolite molded product.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a highly abrasion-resistant zeolite shaped body and a method for producing the same, and more particularly to a highly abrasion-resistant zeolite shaped body excellent in high abrasion resistance and high fluidity and a method for producing the same. The highly abrasion-resistant zeolite shaped body of the present invention is useful for applications such as an adsorption / separation agent and a catalyst. [Background technology]

[0002] In recent years, VOC emissions, which are considered to be one of the causative substances of suspended particulate matter and photochemical oxidants, have been restricted, and technology to control VOC emissions has been attracting attention. Zeolite has been attracting attention as a VOC adsorbent. Its skeleton is made of heat-resistant silicon dioxide, so it is easy and safe to adsorb and desorb VOCs at high temperatures, and it has a large specific surface area. On the other hand, when adsorbing VOCs in factories, etc., fixed-bed or fluidized-bed adsorption towers are used, but the adsorbent becomes powdered during loading or adsorption / desorption, which causes equipment troubles and pressure loss, so the adsorbent is required to have high abrasion resistance, but no practical zeolite molded body with high abrasion resistance has been invented. In addition, the fluidity of the agent is important when loading and recovering materials from fixed-bed and fluidized-bed adsorption towers, and in the case of fluidized beds, during adsorption and regeneration. If the fluidity of the agent is low, it takes a long time to load and recover, but no practical zeolite molded body with high fluidity has been invented.

[0003] Several methods are known for increasing the strength of zeolite molded bodies. For example, Patent Document 1 discloses a method of mixing, kneading, and molding A-type or X-type zeolite as the zeolite, kaolin clay or hydrated halloysite as the binder, and CMC (carboxymethyl cellulose) as the thickener or water-retaining agent.

[0004] Patent Document 2 discloses a method of using low-silica X-type zeolite as the zeolite, and multiple types of clay, including kaolin clay, sepiolite clay, attapulgite clay, and bentonite clay, as the binder.

[0005] Patent Document 3 discloses a method of mixing, kneading, and molding 3A type zeolite as the zeolite, kaolin clay as the binder, and condensed phosphate as the inorganic dispersant.

[0006] None of the patent documents has resulted in the invention of a zeolite molded body having practical wear resistance and fluidity, and there is a need for the invention of a zeolite molded body having even higher wear resistance and fluidity. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-87322 [Patent Document 2] Japanese Patent Application Publication No. 11-314913 [Patent Document 3] JP 2001-226167 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention provides a highly wear-resistant zeolite shaped body having higher wear resistance and higher fluidity than conventional zeolite shaped bodies, and a method for producing the same. [Means for solving the problem]

[0009] As a result of intensive research to solve the above problems, the inventors discovered a manufacturing method in which two types of binders, clay and silica sol, are used when producing a zeolite molded body, and also discovered that it is important to control the loose bulk density and sphericity of the zeolite molded body in order to improve the abrasion resistance of the molded body, thereby completing the present invention. That is, the present invention relates to a highly abrasion-resistant zeolite shaped body, which contains 35 to 70 parts by weight of clay, 5 to 40 parts by weight of silica sol, and 0.5 to 10 parts by weight of a water-soluble sodium salt per 100 parts by weight of zeolite, and which has an abrasion resistance strength of 90% or more, an angle of repose of 40° or less, a loose bulk density of the surface of the zeolite shaped body of 0.5 kg / L or more, and a sphericity of the zeolite shaped body of 1 to 3, and which is characterized in that the zeolite contains one or more zeolites having a moisture adsorption amount of 10 (g / 100g) or less under conditions of Si / Al2 of 10 to 100,000, 25°C, and a relative pressure of 0.5, and a method for producing the highly abrasion-resistant zeolite shaped body.

[0010] The present invention will be described in detail below.

[0011] The highly wear-resistant zeolite molded body of the present invention contains 35 to 70 parts by weight of clay, 5 to 40 parts by weight of silica sol, and 0.5 to 10 parts by weight of water-soluble sodium salt, per 100 parts by weight of zeolite.

[0012] The amount of clay contained in the highly wear-resistant zeolite molded body is 35 parts by weight or more and 70 parts by weight or less per 100 parts by weight of zeolite (anhydrous equivalent). If it is less than 35 parts by weight, the wear resistance is low, and even if it is more than 70 parts by weight, no improvement in wear resistance is observed. In order to improve the wear resistance, it is preferably 40 parts by weight or more and 60 parts by weight or less, and more preferably 45 parts by weight or more and 55 parts by weight or less. The particle size of the clay is not particularly limited, but is preferably 0.5 μm or more and 30 μm or less as the average particle size. Examples of clay include sepiolite clay, attapulgite clay, palygorskite clay, and bentonite clay.

[0013] The amount of silica sol contained in the highly abrasion-resistant zeolite shaped body is 5 parts by weight or more and 40 parts by weight or less per 100 parts by weight of zeolite (anhydrous equivalent). If it is less than 5 parts by weight, there is no effect on abrasion resistance, and as the amount of silica sol added increases, the abrasion resistance also improves, but if it exceeds 40 parts by weight, the extrusion moldability significantly deteriorates. In order to maintain both abrasion resistance and extrusion moldability at a high level, it is preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less. The particle size of the silica sol is not particularly limited, but the average particle size is preferably 5 nm or more and 30 nm or less.

[0014] The amount of the water-soluble sodium salt contained in the highly wear-resistant zeolite molded body is 0.5 parts by weight or more and 10 parts by weight or less per 100 parts by weight of zeolite (anhydrous equivalent). If it is less than 0.5 parts by weight, the effect is insufficient, and if it is more than 10 parts by weight, the effect does not change. In order not to increase the amount of sodium derived from the water-soluble sodium salt, it is preferably 0.5 parts by weight or more and 8 parts by weight or less, and more preferably 0.5 parts by weight or more and 6 parts by weight or less. Examples of the water-soluble sodium salt include inorganic acid sodium and organic acid sodium.

[0015] The inorganic sodium salt may be any water-soluble sodium salt, such as sodium phosphate, sodium silicate, and sodium aluminate. Of these, sodium phosphate is preferred. Examples of sodium phosphate include sodium monophosphate, sodium diphosphate, sodium triphosphate, sodium pyrophosphate, sodium acid pyrophosphate, sodium tripolyphosphate, sodium tetrapolyphosphate, and sodium hexametaphosphate.

[0016] The organic acid sodium salt may be any water-soluble sodium salt, and examples thereof include general organic carboxylic acids, aminocarbonates, ether carboxylates, vinyl polymer sodium salts, etc. Examples of general organic carboxylic acids include sodium citrate, sodium gluconate, sodium oxalate, sodium tartrate, etc. Examples of aminocarbonates include sodium ethylenediaminetetraacetate, sodium diethylenetriaminopentaacetate, etc. Examples of ether carboxylates include sodium carboxymethyltartronate, sodium carboxymethyloxysuccinate, etc. Examples of vinyl polymer sodium salts include sodium polyacrylate, sodium salt of acrylic acid / maleic acid copolymer, etc.

[0017] The highly abrasion-resistant zeolite molded article of the present invention has an abrasion resistance of 90% or more. If the abrasion resistance is less than 90%, it may be easily pulverized and may easily cause pressure loss. The abrasion resistance is measured according to the activated carbon test method of JIS-K-1474 (see <Abrasion Resistance Test> in the Examples). The abrasion resistance is preferably 92% or more, more preferably 95% or more, and particularly preferably 96.5% or more.

[0018] The highly wear-resistant zeolite shaped body of the present invention has an angle of repose of 40° or less. If the angle of repose exceeds 40°, the fluidity is poor, and it may take a long time to fill and recover the agent. Here, the angle of repose is measured according to <Measurement of angle of repose> in the Examples. The angle of repose is preferably 38° or less, more preferably 36° or less, and particularly preferably 32° or less.

[0019] The high abrasion resistance zeolite shaped body of the present invention has a loose bulk density of 0.5 kg / L or more. If the loose bulk density is less than 0.5 kg / L, the abrasion resistance strength is significantly reduced, and there is a risk that pressure loss due to pulverization may easily occur. Here, the measurement of the loose bulk density is performed according to <Measurement of loose bulk density> in the Examples.

[0020] The highly abrasion-resistant zeolite shaped body of the present invention has a sphericity of 1 or more and 3 or less. If the sphericity exceeds 3, the abrasion resistance strength and fluidity are significantly reduced, and there is a risk that the pressure loss due to powdering may easily occur. Here, the sphericity is measured according to <Measurement of sphericity> in the Examples.

[0021] The zeolite contained in the highly wear-resistant zeolite molded body is a zeolite having Si / Al2 of 10 or more and 100,000 or less, and a water adsorption amount of 10 (g / 100g) or less under the conditions of 25°C and relative pressure 0.5, and contains one or more of these. When Si / Al2 is less than 10 and the water adsorption amount exceeds 10 (g / 100g) under the conditions of 25°C and relative pressure 0.5, the wear strength decreases. Si / Al2 is preferably 50 or more and 10,000 or less, and more preferably 80 or more and 2,000 or less. Examples of the types of zeolite include beta-type zeolite, Y-type zeolite, L-type zeolite, ferrierite-type zeolite, mordenite-type zeolite, and ZSM-5-type zeolite, and Y-type zeolite and ZSM-5-type zeolite are preferred.

[0022] The method for producing a highly wear-resistant zeolite molded body of the present invention (hereinafter also referred to as the "production method of the present invention") is characterized in that, per 100 parts by weight of zeolite, 35 to 70 parts by weight of clay, 5 to 40 parts by weight of silica sol, 0.5 to 10 parts by weight of a water-soluble sodium salt, 4 to 20 parts by weight of a molding aid, and 120 to 180 parts by weight of water are mixed and kneaded to obtain a kneaded mixture, which is molded at a rotation speed of 300 rpm or more, dried, and the obtained zeolite molded body is fired at 400°C to 700°C.

[0023] The kneaded material used in the manufacturing method of the present invention includes clay. Examples of clay include sepiolite clay, attapulgite clay, palygorskite clay, and bentonite clay. The amount of clay is 35 parts by weight or more and 70 parts by weight or less with respect to 100 parts by weight of zeolite (anhydrous equivalent). If it is less than 35 parts by weight, the abrasion resistance is low, and even if it is more than 70 parts by weight, no improvement in abrasion resistance is observed. Since the abrasion resistance is higher, it is preferably 40 parts by weight or more and 60 parts by weight or less, and more preferably 45 parts by weight or more and 55 parts by weight or less. The particle size of the clay is not particularly limited, but is preferably 0.5 μm or more and 30 μm or less as an average particle size.

[0024] The kneaded material used in the manufacturing method of the present invention contains silica sol. The amount of silica sol is 5 parts by weight or more and 40 parts by weight or less per 100 parts by weight of zeolite (anhydrous equivalent). If the amount is less than 5 parts by weight, there is no effect on abrasion resistance, and as the amount of silica sol added increases, the abrasion resistance also improves, but if the amount exceeds 40 parts by weight, the extrusion moldability significantly deteriorates. In order to maintain both abrasion resistance and extrusion moldability at a high level, the amount is preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less. The particle size of the silica sol is not particularly limited, but preferably the average particle size is 5 nm or more and 30 nm or less. The pH is not particularly limited, but preferably 7.0 or more and 10.0 or less.

[0025] The kneaded material used in the manufacturing method of the present invention contains a water-soluble sodium salt. Examples of the water-soluble sodium salt include inorganic acid sodium and organic acid sodium. The water-soluble sodium salt preferably contains at least one of inorganic acid sodium and organic acid sodium. Although the reason is unclear, the use of a water-soluble sodium salt significantly increases the wear resistance. The amount of the water-soluble sodium salt is 0.5 parts by weight or more and 10 parts by weight or less with respect to 100 parts by weight of zeolite (anhydrous equivalent). If it is less than 0.5 parts by weight, the effect is insufficient, and if it is more than 10 parts by weight, the effect does not change. In order not to increase the amount of sodium derived from the water-soluble sodium salt, it is preferably 0.5 parts by weight or more and 8 parts by weight or less, and more preferably 0.5 parts by weight or more and 6 parts by weight or less.

[0026] The inorganic sodium salt may be any water-soluble sodium salt, such as sodium phosphate, sodium silicate, and sodium aluminate. Of these, sodium phosphate is preferably used because it is easy to handle. As the sodium phosphate, for example, sodium monophosphate, sodium diphosphate, sodium triphosphate, sodium pyrophosphate, sodium acid pyrophosphate, sodium tripolyphosphate, sodium tetrapolyphosphate, and sodium hexametaphosphate can be used.

[0027] The organic acid sodium salt may be any water-soluble sodium salt, such as general organic carboxylic acids, aminocarbonates, ether carboxylates, vinyl polymer sodium salts, etc. Examples of general organic carboxylic acids that can be used include sodium citrate, sodium gluconate, sodium oxalate, sodium tartrate, etc. Examples of aminocarbonates that can be used include sodium ethylenediaminetetraacetate, sodium diethylenetriaminopentaacetate, etc. Examples of ether carboxylates that can be used include sodium carboxymethyltartronate, sodium carboxymethyloxysuccinate, etc. Examples of vinyl polymer sodium salts that can be used include sodium polyacrylate, sodium salt of acrylic acid / maleic acid copolymer, etc.

[0028] The kneaded material used in the manufacturing method of the present invention contains a molding aid. The molding aid is one that improves moldability, and examples thereof include cellulose, alcohol, lignin, starch, and guar gum. Of these, cellulose and alcohol are preferred because they are easy to handle. Examples of cellulose include crystalline cellulose, hydroxypropylmethylcellulose, and sodium carboxymethylcellulose (CMC). Examples of alcohol include polyvinyl alcohol and ethylene glycol. The amount of the molding aid is 4 parts by weight or more and 20 parts by weight or less, and preferably 8 parts by weight or more and 16 parts by weight or less, relative to 100 parts by weight of zeolite (anhydrous equivalent). If it is less than 4 parts by weight, the abrasion resistance decreases, and if it exceeds 20 parts by weight, the moldability decreases significantly.

[0029] The amount of water contained in the kneaded product used in the production method of the present invention is 120 parts by weight to 180 parts by weight, preferably 140 parts by weight to 160 parts by weight, based on 100 parts by weight of zeolite (anhydrous equivalent). If the amount is less than 120 parts by weight or more than 180 parts by weight, molding may become difficult.

[0030] The zeolite contained in the kneaded product used in the manufacturing method of the present invention must contain at least one zeolite having a Si / Al2 of 10 or more and 100,000 or less, and a moisture adsorption amount of 10 (g / 100g) or less under the conditions of 25°C and relative pressure 0.5. When the Si / Al2 is less than 10 and the moisture adsorption amount exceeds 10 (g / 100g) under the conditions of 25°C and relative pressure 0.5, moisture in the air is easily adsorbed and the abrasion strength is reduced. Si / Al2 is preferably 50 or more and 10,000 or less, more preferably 80 or more and 2,000 or less. Examples of the types of zeolite include beta-type zeolite, Y-type zeolite, L-type zeolite, ferrierite-type zeolite, mordenite-type zeolite, and ZSM-5-type zeolite, and Y-type zeolite and ZSM-5-type zeolite are preferred.

[0031] The kneaded product used in the manufacturing method of the present invention is obtained by mixing 35 to 70 parts by weight of clay, 5 to 40 parts by weight of silica sol, 0.5 to 10 parts by weight of water-soluble sodium salt, 4 to 20 parts by weight of molding aid, and 120 to 180 parts by weight of water, relative to 100 parts by weight of zeolite, and then kneading. There are no particular limitations on the method of mixing and kneading, and for example, a roll kneader Mixmarer, a blade stirring Henschel mixer, a batch or continuous kneader, etc. can be used.

[0032] The manufacturing method of the present invention is to mold the kneaded material obtained as described above at a rotation speed of 300 rpm or more. More specifically, the kneaded material obtained is molded into a cylindrical shape, and then molded at a rotation speed of 300 rpm or more in a molding machine. If the rotation speed is less than 300 rpm, the sphericity tends to be high and the abrasion resistance tends to be low. The rotation speed is preferably 450 rpm or more, and more preferably 600 rpm or more.

[0033] The kneaded mixture obtained can be formed into a cylindrical shape by, for example, rolling granulation, stirring granulation, extrusion molding, spray granulation, etc., with extrusion molding being preferred.

[0034] Examples of molding machines used in the method of molding at a rotation speed of 300 rpm or more include molding machines for rolling granulation, rolling granulation, stirring granulation, spray granulation, etc., and a molding machine for rolling granulation is preferred.

[0035] The shape of the molded body obtained by the manufacturing method of the present invention is not particularly limited, but is preferably spherical (including approximately spherical, the same applies below), cylindrical, elliptical, bale-shaped, trefoil-shaped, ring-shaped, etc., and is more preferably spherical or cylindrical. The size of the molded body is not particularly limited, but the average particle size is preferably 0.1 μm or more and 3 mm or less. Methods for improving the yield during molding include pre-drying, etc. For example, pre-drying can be performed by air drying, vibration drying, rolling granulation, surface drying, or a combination of two or more of these methods. The moisture content after pre-drying may be any moisture content that allows molding after pre-drying, and is preferably 40% or more and 60% or less.

[0036] The shaped zeolite body is dried. There is no particular limitation on the drying method, and for example, a box dryer, a continuous dryer, etc. can be used. The drying temperature can be 50°C or higher and 200°C or lower. The drying atmosphere can be air or nitrogen atmosphere under atmospheric pressure. The dried zeolite body is classified into the desired size. Classification can also be performed before drying.

[0037] The dried zeolite molded body is calcined. The calcination method is not particularly limited, and can be performed, for example, in a box-type muffle furnace, a rotary kiln, a shaft kiln, or the like. The calcination temperature may be any temperature at which the fibrous clay can be sintered to develop strength, and is preferably 400°C to 700°C. The calcination atmosphere can be air or nitrogen atmosphere under atmospheric pressure. Effect of the Invention

[0038] The highly wear-resistant zeolite shaped body of the present invention has high wear resistance and fluidity and is therefore particularly useful in adsorption / separation applications including thermal regeneration processes and catalytic reaction applications. EXAMPLES

[0039] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0040] <Measurement of water adsorption amount> The amount of water adsorption was measured at 25°C using a spring balance type adsorption device.

[0041] <Wear resistance test> The abrasion resistance test was performed according to JIS-K-1474. That is, the sample was filled into a 200mL graduated cylinder up to the 100mL mark by tapping it lightly. The sample was weighed out in the graduated cylinder and placed in an abrasion resistance test dish together with 15 steel balls of 12.7mm and 9.5mm diameters. The dish was attached to a sieve shaker and shaken for 30 minutes. All the sample except the steel balls was placed in a sieve and receiver with half the mesh size of the sieve with the most sample remaining, and the dish was attached to the sieve shaker. After shaking for 3 minutes, the mass of the sample remaining on the sieve and in the receiver was weighed to the nearest 0.1g. The abrasion resistance was calculated by the following formula 1.

[0042] H=W / S×100…(Formula 1) Here, H is the abrasion resistance strength (mass fraction %), W is the mass (g) of the sample remaining on the sieve, and S is the total mass (g) of the sample remaining on the sieve and on the tray.

[0043] <Measurement of angle of repose> The angle of repose was measured using a powder tester (manufactured by Hosokawa Micron).

[0044] <Measurement of loose bulk density> Approximately 100 g of the sample, weighed to an accuracy of 0.1%, was gently placed in a dry 250 mL measuring cylinder (minimum graduation unit: 2 mL) without compaction. If necessary, the upper surface of the powder bed was carefully smoothed without compaction, the loose bulk volume was read to the minimum graduation unit, and the loose bulk density (kg / L) was calculated from the loose bulk volume.

[0045] <Measurement of sphericity> The sphericity was measured by photographing the zeolite molded body using a digital microscope (VHX-5000, Keyence Corporation) and then measuring the long and short diameters of the zeolite molded body. The sphericity (long diameter / short diameter) was calculated from the measured long and short diameters. This characteristic value was the average value of the measurements of 50 zeolite molded bodies.

[0046] Example 1 80 parts by weight (1627 g, moisture content: 2%) of Y-type zeolite powder (HSZ (registered trademark)-385HUA, manufactured by Tosoh (Si / Al2: 100, moisture adsorption amount: 2 g / 100 g)), 20 parts by weight (413 g, moisture content: 3%) of MFI-type zeolite powder (HSZ (registered trademark)-891HOA, manufactured by Tosoh (Si / Al2: 1500, moisture adsorption amount: 4 g / 100 g)), 50 parts by weight (1253 g, moisture content: 22%) of attapulgite-type clay (Minigel MB, manufactured by Active Minerals), 6 parts by weight (120 g) of sodium carboxymethylcellulose (molding aid, Cellogen, manufactured by Daiichi Kogyo Seiyaku), and 6 parts by weight (120 g) of crystalline cellulose (Ceolas (registered trademark) RC-591, manufactured by Asahi Kasei Chemicals) were weighed out and mixed with a mix muller (manufactured by Shinto Kogyo) for 5 minutes. 1639 g of silica sol (Snowtex C-30, average particle size: 12 nm, pH: 8.7, manufactured by Nissan Chemical) was added and mixed for 5 minutes. 1000 g of water in which 1.5 parts by weight (30 g) of sodium dihydrogen phosphate (NaH2PO4, manufactured by Rinkagaku Kogyo) was dissolved was added and mixed for 5 minutes. Then, 960 g of water was further added and the mixture was stirred and kneaded for 80 minutes to obtain a kneaded product. The ignition loss of the kneaded product obtained was measured under conditions of 650°C and 1 hour, and the result was 103 parts by weight per 100 parts by weight of zeolite. The kneaded product obtained was molded into a cylindrical shape with a diameter of 0.6 mm, and then rolled and granulated using a Marumerizer (QJ-400, manufactured by Dalton) at a rotation speed of 900 rpm, and the cylindrical molded body was molded into a spherical shape. The mixture was dried at 100°C for 12 hours or more, and then calcined at 650°C for 3 hours to obtain a zeolite molded body (50 parts by weight of clay, 25 parts by weight of silica sol, 1.5 parts by weight of water-soluble sodium salt, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g, relative to 100 parts by weight of zeolite). The angle of repose of the zeolite molded body was 31°, the loose bulk density was 0.59kg / L, and the sphericity was 1.3.

[0047] After the abrasion resistance test, the abrasion resistance strength was 95.5%.

[0048] Example 2 A kneaded product was obtained by the same operation as in Example 1. The ignition loss of the kneaded product obtained was measured at 650°C for 1 hour, and was found to be 103 parts by weight per 100 parts by weight of zeolite. The kneaded product obtained was molded into a cylindrical shape with a diameter of 0.6 mm, and then subjected to rolling and granulation at a rotation speed of 600 rpm in a Marumerizer (QJ-400, manufactured by Dalton), to mold the cylindrical molded body into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 25 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g) relative to 100 parts by weight of zeolite. The angle of repose of the zeolite molded body was 36°, the loose bulk density was 0.56kg / L, and the sphericity was 1.6.

[0049] After the abrasion resistance test, the abrasion resistance strength was 92.9%.

[0050] Example 3 A kneaded product was obtained by the same operation as in Example 1. The ignition loss of the kneaded product obtained was measured at 650°C for 1 hour, and was found to be 103 parts by weight per 100 parts by weight of zeolite. The kneaded product obtained was molded into a cylindrical shape with a diameter of 0.6 mm, and then subjected to rolling and granulation at a rotation speed of 300 rpm in a Marumerizer (QJ-400, manufactured by Dalton), to mold the cylindrical molded body into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 25 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g) relative to 100 parts by weight of zeolite. The angle of repose of the zeolite molded body was 38°, the loose bulk density was 0.52kg / L, and the sphericity was 2.6.

[0051] After the abrasion resistance test, the abrasion resistance strength was 90.8%.

[0052] Example 4 A mixture was obtained by the same operation as in Example 1, except that the kneader was changed to a Henschel mixer. The ignition loss of the obtained mixture was measured at 650°C for 1 hour, and was found to be 101 parts by weight per 100 parts by weight of zeolite. The obtained mixture was molded into a cylindrical shape with a diameter of 0.6 mm, and then subjected to rolling and granulation at a rotation speed of 900 rpm in a Marmerizer (QJ-400, manufactured by Dalton), to mold the cylindrical molded body into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 25 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g) relative to 100 parts by weight of zeolite. The angle of repose of the zeolite molded body was 31°, the loose bulk density was 0.59, and the sphericity was 1.3.

[0053] After the abrasion resistance test, the abrasion resistance strength was 92.3%.

[0054] Example 5 A kneaded product was obtained by the same operation as in Example 1, except that the silica sol was 10 parts by weight (653 g), the carboxymethylcellulose sodium was 4 parts by weight (80 g), the crystalline cellulose (Ceolas (registered trademark) RC-591, manufactured by Asahi Kasei Chemicals) was 4 parts by weight (80 g), and the water added was 1350 g. The ignition loss of the kneaded product obtained was measured under conditions of 650 ° C. and 1 hour, and was 95 parts by weight per 100 parts by weight of zeolite. The kneaded product obtained was molded into a cylindrical shape with a diameter of 0.6 mm, and then rolled and sized using a Marumerizer (QJ-400, manufactured by Dalton) at a rotation speed of 900 rpm, and the cylindrical molded body was molded into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 10 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g, relative to 100 parts by weight of zeolite). The angle of repose of the zeolite molded body was 28°, the loose bulk density was 0.65, and the sphericity was 1.4.

[0055] After the abrasion resistance test, the abrasion resistance strength was 94.0%.

[0056] Example 6 The same operation as in Example 1 was carried out to obtain a kneaded product. The ignition loss of the obtained kneaded product was measured under conditions of 650°C and 1 hour, and was 103 parts by weight per 100 parts by weight of zeolite. The obtained kneaded product was molded into a cylindrical shape with a diameter of 0.6 mm, pre-dried in a turbo comminutor to adjust the moisture content to 49%, and rolled and sized in a marumerizer (QJ-400, manufactured by Dalton) at a rotation speed of 300 rpm to form a cylindrical molded body into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 25 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g) relative to 100 parts by weight of zeolite. The angle of repose of the zeolite molded body was 28°, the loose bulk density was 0.58kg / L, and the sphericity was 1.5.

[0057] After the abrasion resistance test, the abrasion resistance strength was 94.2%.

[0058] Comparative Example 1 A kneaded product was obtained by the same operation as in Example 1. The ignition loss of the kneaded product obtained was measured under conditions of 650°C and 1 hour, and was found to be 103 parts by weight per 100 parts by weight of zeolite. The kneaded product obtained was molded into a cylindrical shape with a diameter of 0.6 mm, and then subjected to rolling and granulation at a rotation speed of 100 rpm in a Marumerizer (QJ-400, manufactured by Dalton), to mold the cylindrical molded body into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 25 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g) relative to 100 parts by weight of zeolite. The angle of repose of the zeolite molded body was 42°, the loose bulk density was 0.47kg / L, and the sphericity was 3.1.

[0059] After the abrasion resistance test, the abrasion resistance strength was 86.3%.

[0060] Comparative Example 2 A kneaded product was obtained by the same operation as in Example 1, except that no silica sol was added, 4 parts by weight (80 g) of sodium carboxymethylcellulose, 4 parts by weight (80 g) of crystalline cellulose (Ceolas (registered trademark) RC-591, manufactured by Asahi Kasei Chemicals), and 1740 g of water were added. The ignition loss of the kneaded product obtained was measured at 650°C for 1 hour, and was 95 parts by weight per 100 parts by weight of zeolite. The kneaded product obtained was molded into a cylindrical shape with a diameter of 0.6 mm, and then rolled and sized in a Marumerizer (QJ-400, manufactured by Dalton) at a rotation speed of 900 rpm to mold the cylindrical molded body into a spherical shape. After that, it was dried at 100℃ for 12 hours or more, and then calcined at 650℃ for 3 hours to obtain a zeolite molded body (clay: 50 parts by weight, silica sol: 0 parts by weight, water-soluble sodium salt: 1.5 parts by weight, Si / Al2 of zeolite (385HUA): 100, Si / Al2 of zeolite (891HOA): 1500, water adsorption amount of zeolite (385HUA): 2g / 100g, water adsorption amount of zeolite (891HOA): 4g / 100g) relative to 100 parts by weight of zeolite. The angle of repose of the zeolite molded body was 31°, the loose bulk density was 0.55kg / L, and the sphericity was 1.3.

[0061] After the abrasion resistance test, the abrasion resistance strength was 84.9%. [Industrial Applicability]

[0062] The highly wear-resistant zeolite molded body of the present invention has excellent wear resistance and can be used in applications such as adsorption / separation agents and catalysts without causing equipment trouble or pressure loss, and has excellent fluidity and can be easily filled, recovered, etc., when used in fixed-bed or fluidized-bed adsorption towers.

Claims

1. A highly abrasion-resistant zeolite molded body containing 35 to 70 parts by weight of clay, 5 to 40 parts by weight of silica sol, and 0.5 to 10 parts by weight of a water-soluble sodium salt relative to 100 parts by weight of zeolite, and having an abrasion resistance strength of 90% or more, an angle of repose of 40° or less, a loose bulk density of the surface of the zeolite molded body of 0.5 kg / L or more, and a sphericity of the zeolite molded body of 1 to 3, wherein the zeolite is Si / Al 2 1. A highly wear-resistant zeolite molded product comprising one or more zeolites having a water adsorption amount of 10 (g / 100 g) or less under the conditions of a molecular weight of 10 or more and 100,000 or less at 25° C. and a relative pressure of 0.

5.

2. 2. The highly wear-resistant zeolite molded article according to claim 1, wherein the zeolite comprises at least one of beta zeolite, Y zeolite, L zeolite, ferrierite zeolite, mordenite zeolite, and ZSM-5 zeolite.

3. The method comprises mixing 35 to 70 parts by weight of clay, 5 to 40 parts by weight of silica sol, 0.5 to 10 parts by weight of a water-soluble sodium salt, 4 to 20 parts by weight of a molding aid, and 120 to 180 parts by weight of water, per 100 parts by weight of zeolite, and kneading the mixture to obtain a kneaded product, molding the kneaded product at a rotation speed of 300 rpm or more, drying the product, and firing the resulting zeolite molded body at 400° C. or more and 700° C. or less, wherein the zeolite is Si / Al 2 3. The method for producing a highly abrasion-resistant zeolite molded body according to claim 1, further comprising one or more zeolites having a molecular weight of 10 or more and 100,000 or less and a moisture adsorption amount of 10 (g / 100 g) or less under conditions of 25° C. and a relative pressure of 0.

5.

4. 4. The method for producing a highly wear-resistant zeolite molded article according to claim 3, wherein the zeolite comprises at least one of beta zeolite, Y zeolite, L zeolite, ferrierite zeolite, mordenite zeolite, and ZSM-5 zeolite.

Citation Information

Patent Citations

  • Granular zeolite with wear resistance and its manufacture

    JP1982149818A

  • High strength and low wear zeolite granule, its production and adsorption separation method using same

    JP1998087322A

  • High strength low wear zeolite granule and its production

    JP1999314913A

  • Zeolite formed bead, production process of the same and adsorption / Removal process using the same

    JP2001226167A

  • Zeolite structure and production method thereof

    JP2011201722A